ANALISIS FINANSIAL POLA AGROFORESTRY PADA KHDTK BORISALLO, KABUPATEN GOWA, SULAWESI SELATAN - Wakka, Abdul Kadir; Hayati, Nur (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
The research objective is to seek the financial feasibility of land management patterns conducted by the local community which implement agro forestry technologies. This research conducted at the Forest Area Special Purpose (KHDTK) Borisallo, located in sub-distric of Bontoparang, Parangloe, and Gowa. The data have been obtained and analyzed use a descriptive approach to their feasibility. The results showed land management of agro forestry patterns in KHDTK Borisallo is feasible to develop at 12% interest rate. The proportion of agro forestry land use is with 30% cacao and 70% coffee crops is more feasible to be developed in comparation with another agro forestry patterns.